Religion and justice in Túpac Amaru - Klaiber, Jeffrey (1982)
Little has been written about the religious meaning of the Túpac Amaru movement. However, it seems clear that one of the most important motives that inspired this great indigenous rebellion and that formed the background of all the actions of José Gabriel Condorcanqui was a strong messianic feeling, where Inca elements were mixed and confused with Christian elements. The Spanish, of course, condemned the rebellion as an act of treason against the King and disobedience against God.